2020
DOI: 10.1093/jxb/eraa348
|View full text |Cite
|
Sign up to set email alerts
|

Maize pentatricopeptide repeat protein DEK53 is required for mitochondrial RNA editing at multiple sites and seed development

Abstract: Pentatricopeptide repeat (PPR) proteins were identified as site-specific recognition factors for RNA editing in plant mitochondria and plastids. In this study, we characterized maize (Zea mays) kernel mutant defective kernel 46 (dek46), which has lethal embryo and collapsed endosperm. Dek46 encodes an E-subgroup PPR protein which possesses a short PLS repeat region of only seven repeats. Subcellular localization analysis indicated that DEK46 is localized in mitochondrion. The strand- and transcript-specific RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 112 publications
2
30
0
1
Order By: Relevance
“…DEK55 is necessary for C-to-U editing of multiple sites in the mitochondrial transcripts of maize PPR proteins, including DYW2, EMP21, NUWA, MEF8, and DEK53, are involved in C-to-U editing at multiple sites [48][49][50][51][52]. In this study, we demonstrated that DEK55 participated in RNA editing at 31 sites, while the editing ratio of 24 editing sites was reduced and that of seven editing sites was increased in dek55, suggesting that DEK55 is also necessary for RNA editing at multiple sites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DEK55 is necessary for C-to-U editing of multiple sites in the mitochondrial transcripts of maize PPR proteins, including DYW2, EMP21, NUWA, MEF8, and DEK53, are involved in C-to-U editing at multiple sites [48][49][50][51][52]. In this study, we demonstrated that DEK55 participated in RNA editing at 31 sites, while the editing ratio of 24 editing sites was reduced and that of seven editing sites was increased in dek55, suggesting that DEK55 is also necessary for RNA editing at multiple sites.…”
Section: Discussionmentioning
confidence: 99%
“…EMP21 contains 11 PPR-motifs in addition to E and DYW domains and belongs to PPR-DYW proteins [51]. DEK53 is an E-subgroup PPR protein with seven PPR repeats [52]. DEK55 is considered as an E-subgroup PPR protein that contains the canonical E domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations